Study on Preparation and Characterization of Cross-linked b-Cyclodextrin Polymers with Hexamethylene Diisocyanate in Ultrasonic - Zhou, Yu-Qing; Huang, Juan; Han, Ping-Fang; Lv, Xiao-Ping (Asian Journal of Chemistry, 2012)
Through modifying b-cyclodextrin (b-CD) with diisocyanate in ultrasonic conditions, the cross-linked polymer of the modified cyclodextrin was produced. The main influencing factors and optimum synthesis technological conditions of diisocyanate modified cyclodextrin were selected via orthogonal experimental method and by taking the yield of cross-linked polymer as an evaluation index: the mole ratio of n (isocyanate): n (b-CD) was about 1:9; hexamethylene diisocyanate (HDI) was employed as diisocyanate; ultrasonic intensity, 0.1 W cm-2; reaction temperature, 60 ºC; and reaction time was 7 h. After characterizing the cross-linked polymer by means of such test methods as infrared spectrum, scanning electron microscope and thermogravimetric analysis, the result indicated that the modified b-cyclodextrin kept the original cavity structure; the cyclodextrin generated carbamic acid ester base bond through reaction with the diisocyanate and the cross-linked polymer is in a network structure. The synthesis of cyclodextrin polymer in ultrasonic conditions might reduce the reaction temperature and shorten the reaction time and the cross-linked polymer formed a microspheric multi-cavity structure.